The effect of human periodontal pathogenic bacteria on immediate basal implant placement: A comparative study in beagle dogs - Ali Dakheel; Ismaeil Mammani; Jiyar Naji (The Scientific Temper, 2024)
This study can clarify and compare two lines of the same design of basal implants based on microbiological criteria. Ten beagle dogs were involved in the first stage of the study when swabs from the gingival sulci were collected before extraction of the first and second premolars in both maxillary and mandibular segments of the left side of the mouth, followed by immediate implant placement of bicortical screws and compression screws of the basal implants. A waiting period of four months was followed by swab collection from the peri-implant areas of the successful implants of eight dogs. The swabs were sent for a qualitative polymerase chain reaction (PCR) technology to detect five periodontopathogens. In the first stage of the study, detecting some bacterial species can be correlated to the surgical results of the failure rate already detected. In the second stage, the prevalence of specific bacterial species was more significant compared to the first stage of the study, and the detected bacterial percentage was also higher. Periodontopathogens play an important role in peri-implant postoperative infection and subsequent failure, whether individually or even together.